“I Can Know More Vocabularies and Their Meanings”: EFL Students’ Perceptions on the Impact of English Translation of Islamic Verses on Incidental Vocabulary Acquisition in English Lessons about Nature - Saiful, Jepri Ali (Journal of English Teaching and Learning Issues, 2024)
There is a paucity of knowledge on the use of Islamic holy references in English on learners’ Incidental Vocabulary Acquisition (IVA). This study aimed to investigate English students’ perceptions regarding the use of English translations of Islamic verses related to nature on students’ IVA. The study involved 77 senior high school students, consisting of 48 females and 29 males, from three schools in Surabaya and Pemalang, Indonesia. A case study design was employed, incorporating quantitative and qualitative data. Closed and open-ended questionnaires were the instruments, and the data were analyzed through descriptive methods and content analysis. The integrated findings showed that students viewed the potential effectiveness of English verses from the Qur’an and Sunnah in developing their understanding of IVA, Islam, and nature. Moreover, they expressed satisfaction with this approach to learning. In conclusion, students perceive that English verses from Islamic references offer significant benefits for their IVA.